EFEKTIVITAS BEBERAPA PRODUK PEMBERSIH WAJAH ANTIACNE TERHADAP BAKTERI PENYEBAB JERAWAT Propionibacterium acnes - marliana, Marliana; Sartini, Sartini; Karim, Abdul (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2018)
The purpose of this study was to determine the effectiveness of some antiacne facial cleanser products against bacteria that cause acne Propionibacterium acnes, which conducted experimentally using 6 product against of antiacne facial cleanser bacteria cause Propionibacterium acnes with three replication. The parameters observed were the inhibitory zone diameters. The results showed that of some antiacne facial cleanser products that are most effective in inhibiting the growth of acne-causing bacteria Propionibacterium acnes is the product CCA code, with a 35 mm inhibit zone, because CCA products were contain 6 combinations of natural ingredients from Hamamelis virginia, Melaleuca alternifolia, Cinnamomum zeylanicum, Cedrus atlantica, Portulaca oleracea and olive oil All antiacne products are shown to have effectiveness against the bacteria Propionibacterium acnes.